Assessing industry 5.0 readiness—Prototype of a holistic digital index to evaluate sustainability, resilience and human-centered factors - Anja Brückner; Mandy Wölke; Franziska Hein-Pensel; Edgar Schero; Heiner Winkler; Iren Jabs (International Journal of Information Management Data Insights)
The European Commission introduced Industry 5.0, marking a paradigm shift in its strategic vision that differs from its predecessor in emphasizing social and sustainable factors. Consequently, a comprehensive reassessment of the social role of industry is inevitable. The European Commission has recognized the conceptual gap in the implementation of Industry 5.0. It recommends the development of technology roadmaps and new tools, including assessments, to guide organizations through this paradigm shift. The aim of this paper is threefold. First, characterizations of the new components of Industry 5.0 are provided to establish a baseline understanding. Second, an approach to measuring the maturity of Industry 5.0 is developed, considering the complexity of Industry 5.0. Third, the prototypical development of an innovative assessment, called the Digital Index, is presented. The assessment tool will offer an approach for companies to examine the requirements for Industry 5.0 and realize them with the use of practical recommendations.